Double-Sided Moral Hazard, Efficiency Wages and Litigation - Oliver Gürtler; Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
We consider a double-sided moral hazard problem where each party can renege on the signed contract since there does not exist any verifi- able performance signal. It is shown that ex-post litigation can restore incentives of the agent. Moreover, when the litigation can be settled by the parties the pure threat of using the legal system may suffice to make the principal implement first-best effort. As is shown in the paper, this finding is rather robust. In particular, it holds for sit- uations where the agent is protected by limited liability, where the parties have different technologies in the litigation contest, or where the agent is risk averse.
Keywords: D86; J33; K41; 330; double-sided moral hazard; efficiency wage; litigation contest; settlement; Arbeitsvertrag; Vertragstheorie; Moral Hazard; Zivilprozess; Anreizvertrag; Effizienzlohn; Theorie